A case report of bicornis bicollis uterus with unilateral cervical atresia: an unusual aetiology of chronic debilitating pelvic pain in a Cameroonian teenager - Julius Sama Dohbit; Esther Meka; Joel Noutakdie Tochie; Igor Kamla; Darolles Mwadjie; Pascal Foumane (BMC, 2017)
Abstract Background Congenital uterine anomalies like bicornis or bicornuate uterus are relatively rare in sub-Saharan Africa. They are associated with an increased rate of spontaneous abortion, preterm delivery, and infertility. The occurrence of bicornis bicollis uterus with unilateral cervical atresia is exceptional and its management is controversial. We hereby report a rare cause of chronic pelvic pain in a Cameroonian teenager due to unilateral obstructive hematometra and hematosalpinx in the non-communicating horn of a bicornis bicollis uterus. Case presentation A 13-year-old premenarchal non-virgin female presented with chronic and severe cyclical crampy pelvic pain. On clinical examination, she had a perforated hymen, a single vagina, and one uterine cervix. A two-dimensional pelvic ultrasonography revealed hematometra but missed out the underlying anomaly. Failure to drain the hematometra by serial cervical dilatations prompted an exploratory laparotomy which revealed: bicornis bicollis uterus with a right rudimentary uterine horn communicating with the vagina and a left non-communicating uterine horn distended by hematometra due to a homolateral cervical atresia. She underwent utero-vaginal canalization and a left hemi-hysterotomy with drainage of the hematometra. The postoperative period was uneventful. Regular cyclic menses occurred thereafter beginning at the first postoperative month. She had complete resolution of symptoms without recurrence after six months. Conclusion Due to the risk of compromised fertility from bicornis uterus and the diagnostic challenges akin to resource-limited settings, we highlight the need for a high index of suspicion by healthcare providers when faced with chronic pelvic pain in premenarchal adolescents.